Micropropagation of an Eucalyptus hybrid (Eucalyptus benthamii x Eucalyptus dunnii) - Gilvano Ebling Brondani (Acta Scientiarum. Agronomy, 2011)
This study was designed to micropropagate E. benthamii x E. dunnii, by testing chlorine concentrations for explant asepsis, the optimal concentrations of benzylaminopurine (BAP) and naphthaleneacetic acid (NAA) for bud proliferation, and the ratio between BAP and gibberellic acid (GA3) in two nutrient media for shoot elongation. Nodal segments from H12, H19 and H20 clones were disinfected with 0.5, 1.0, 1.5 and 2.0% (v v-1) of chlorine. Explants were grown on ½MS medium supplemented with BAP (0, 0.25, 0.50, 0.75 and 1.00 mg L-1) and NAA (0, 0.025, 0.050, 0.075 and 0.100 mg L-1) for bud production. They were elongated on MS and ½MS media supplemented with BAP (0, 0.05 and 0.10 mg L-1) and GA3 (0, 0.1, 0.2 and 0.3 mg L-1). The 0.50 mg L-1 BAP and 0.050 mg L-1 NAA combination was optimal for bud proliferation for H12 and H20. GA3 concentrations of 0.10 and 0.20 mg L-1 combined with 0.10 mg L-1 BAP on ½MS resulted in the longest shoots, for H12 and H20, respectively. Regardless of clone, the rooting rate was low, with an average of 12.0% and 14.4% of plants having roots for in vitro and ex vitro conditions, respectively.